Ionic conductivity by correlated barrier hopping in NH4I doped chitosan solid electrolyte - Majid, Siti Rohana; Arof, Abdul Kariem; Buraidah, M.H.; Teo, L.P. (Elsevier, 2009)
Chitosan-NH4I and chitosan-NH4I-EC films have been prepared by solution cast technique. The sample containing 45 wt% ammonium iodide (NH4I) exhibited the highest room temperature conductivity of 3.7.10(-7) S cm(-1). The conductivity of the sample increased to 7.6 x 10(-6) S cm(-1) when 40wt% ethylene carbonate (EC) was added to the 55 wt% chitosan-45 wt% NH4I sample. The conductivity-temperature relationship is Arrhenian. From dielectric loss variation with frequency, the power law exponent was obtained. The temperature dependence of the power law exponent for chitosan-NH4I system follows the correlated barrier hopping (CBH) model while conduction mechanism of the plasticized system can be represented by the small polaron hopping (SPH) model. (C) 2009 Elsevier B.V. All rights reserved.